Selected Bibliocentric and Socio-Cultural Practices and Necessity of Inculturation Hermeneutics in the Yoruba Context - Alabi, David O.; Tukasi, Emmanuel O.; Isaac, Ubong I.; Olufemi, Olukunle O.; Tunase, Christian T.; Olowookere, Adenike F. (NIU Journal of Humanities, 2024)
Certain cultural practices were allowed by Yahweh of Israel in order to pass His message to His people. In this regard, the Canaanite cultural influences and environmental factors on some Jewish conceptions about their God, Yahweh Elohim could not be covered. Examples are attributing meteorological features to Yahweh in the Sinaitic and Exodus Traditions, such as “pillars of cloud”, “fire”, “sounding of trumpets”, a reminiscence of thunder from Baal, the active god of the Canaanites, mountain patronage, theophoric names, building of altars and sacrificing on them to God and the rest of them could not be denied in order to show elements of inculturation and enculturation. It examined the gap that Christianity and its mission activities cannot only be hermeneutically spread through Eurocentric hermeneutics, which would amount to a fallacy, and which would make Christianity a foreign religion to the Africans that has no bearing to the African religious sensibilities and existential needs. This study filled this gap by drawing attention of the Africans to similar cultural practices in the Bible as they have the same and demonstrated that God of the Bible is also for the Africans. It also focused on the selected bibliocentric cultural practices found on the pages of the Judeo-Christian sacred text in the African context. It examined these cultural practices during the biblical world and juxtaposed them with similar African cultural practices. We located where certain biblical practices are similar to the African socio-cultural practices and how it could better illustrate the teaching of the Bible to the Africans with the tool of “inculturation hermeneutics” for the exegetes. Finally, it argues for the necessity of inculturation hermeneutics and summed up that inculturation hermeneutics is the lasting solutions to entrenching biblical hermeneutics to the Africans and the survival of Christianity in this century.